RELATIONSHIP OF HOW PARENTS EDUCATE CHILDREN WITH THE ABILITY TO TAKE THE DECISION OF NURSING STUDENTS - Nurul Huda; Bagus Dwi Cahyono; Mukhammad Toha (Nurse and Health: Jurnal Keperawatan, 2020)
Background: The family is the most basic social institution to print human qualities, even the good and bad development of children determining by the formation of a person in the family. One of the tasks of child development is achieving decision-making abilities. But the fact is that teenagers who are represented by students often do the wrong thing because of their inability to make the right decision. The action can be non-academic or academic. The phenomenon of how to educate children at this time is also getting worse, and this can seek from the increasing number of cases of violence against children.Objectives: The purpose of this study was to determine the relationship between parents' educational patterns and decision-making abilities in nursing students at the Nursing Academy of Pasuruan.Methods: This research used observational analytic study with a cross-sectional design. The population was the student of Nursing Academy Pasuruan as many as 200 students. A sample of 80 students were selected by simple random sampling. Data were collected using two questionnaires that have been tested for validity and reliability, with item-total correlations > 0.20 and Cronbach alpha > 0.60 and analyzed by Spearman ranks.Results: The results of the study found that there is a relationship between parents' educational patterns and decision-making abilities in nursing students (p > 0.05). Positive experiences will encourage children to continue to look for better decision-making strategies in the future.Conclusion: Further research on parents' educational patterns needs to be done with more holistic measurements, namely relating to efforts to meet biological, psychological, social, and spiritual needs. Keywords: Parents’ Educational Patterns, Decision-Making Abilities, Nursing Students